Moisture-Responsive Cellulose For 4D Printing - Bassam AL NAHARI; Khalid ZARBANE; Zitouni BEIDOURI (Incertitudes et Fiabilité des Systèmes Multiphysiques)
Particularly focusing on 4D printing, a technology enabling objects to transform over time. We explore smart materials, emphasizing moisture-responsive variants crucial for 4D printing. Notably, cellulose emerges as key, offering renewable and sustainable bio-based filaments. We detail the meticulous preparation of cellulose from sugarcane bagasse, obtaining high-purity fibers essential for 4D printing. These filaments exhibit versatile stiffness and moisture responsiveness, crucial for hygromorphic structures. Our proposed method integrates a codesign approach tailored for 4D printing, utilizing fused filament fabrication and cellulose-filled filaments. Through this investigation, we uncover cellulose’s potential in sensor technology and additive manufacturing, marking significant progress in responsive materials and 4D printing.